Constructing stable vector bundles from curves with torsion normal bundle - Licanic, Sergio (MATHEMATICA SCANDINAVICA, 2023)
Given a smooth irreducible curve $S$ with torsion normal bundle on a projective surface $X$, we provide a criterion for the non-emptiness of the moduli of slope stable vector bundles with prescribed Chern classes. The criterion is given in terms of the topology of the pair $(X,S)$.